2021
DOI: 10.1386/tmsd_00034_1
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the adoption of SDG reporting by large African and Asian companies

Abstract: This article aims to investigate the adoption of the Sustainable Development Goals (SDGs) by large companies in low- and middle-income countries in Asia and Africa, and the company characteristics that influence them to undertake such new sustainability reporting practices. Logistic regression analyses were applied to combine the data extracted from the Global Reporting Initiative’s Sustainability Disclosure Database and the Orbis database from Bureau van Dijk. The empirical results indicate that characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…However, the empirical evidence is rather mixed. A vast majority of the studies established a positive relationship between gender diversity and sustainability and SDGs reporting (Buallay et al, 2022;Cicchiello et al, 2021;Gir on et al, 2021Gir on et al, , 2022Githaiga & Kosgei, 2022;Injeni et al, 2021;Kazemikhasragh et al, 2021;Kilincarslan et al, 2020;Olayinka, 2022). Interestingly, this relationship can be stronger when female representation on board is between 22% and 50% but may become inverse if it's above 50% (Githaiga & Kosgei, 2022).…”
Section: Firm Corporate Governance Attributesmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the empirical evidence is rather mixed. A vast majority of the studies established a positive relationship between gender diversity and sustainability and SDGs reporting (Buallay et al, 2022;Cicchiello et al, 2021;Gir on et al, 2021Gir on et al, , 2022Githaiga & Kosgei, 2022;Injeni et al, 2021;Kazemikhasragh et al, 2021;Kilincarslan et al, 2020;Olayinka, 2022). Interestingly, this relationship can be stronger when female representation on board is between 22% and 50% but may become inverse if it's above 50% (Githaiga & Kosgei, 2022).…”
Section: Firm Corporate Governance Attributesmentioning
confidence: 99%
“…Board age is likewise linked with sustainability adoption in Africa; however, the finding is mixed. Specifically, Kazemikhasragh et al (2021) found that younger directors are more prone to adopt SDGs reporting. Contrarily, Girón et al (2021) reported that the age of directors does not influence sustainability adoption.…”
Section: Thematic Analysismentioning
confidence: 99%
See 3 more Smart Citations